AGROCLASTER THEORY BASED ON COOPERATION IN ECONOMICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article presents scientific theories about the marketing information system of the Enterprise cluster for the establishment of inter-farm cooperative relations in order to maintain continuous business processes of economic entities of the agro-industrial complex of the economy according to the cluster system, which has recently become increasingly integrated into the system of office work in our country, and its